Facile Fabrication of a Superhydrophobic Surface with Robust Micro-/Nanoscale Hierarchical Structures on Titanium Substrate - Dong, Shuliang (Nanomaterials (Basel), 2020)
A superhydrophobic surface with robust structures on a metallic surface could improve its application in various harsh conditions. Herein, we developed a new strategy to fabricate robust micro-/nanoscale hierarchical structures with electrical discharge machining and electrochemical etching on a titanium substrate. After modification by fluorinated silane, the static water contact angle and slide angle of the surface could reach 162 ± 2° and 4 ± 1°, respectively. The superhydrophobic surfaces showed good corrosion resistance and mechanical stability after scratching with sandpapers. In addition, the superhydrophobic surfaces had good self-cleaning performance even in an acidic environment as well as the potential to be used as guiding tracks in droplet microfluidics and lab-on-a-chip systems. These results are expected to be helpful in designing the surface of liquid float gyroscope parts.